Business Decisions or Corruption? The Business Judgment Rule in Decision 68/2025 - Sahat Parlindungan Simarmata (Politeknik Siber Cerdika Internasional, 2026)
Background: On 20 November 2025, the Anti-Corruption Court at the Central Jakarta District Court delivered Decision Number 68/Pid.Sus-TPK/2025/PN Jkt.Pst, convicting three former directors of PT ASDP Indonesia Ferry (Persero) of corruption arising from a business cooperation arrangement and the acquisition of PT Jembatan Nusantara (2019–2022), with state losses set at IDR 1.25 trillion. Objective: This study examines the juridical construction of the Business Judgment Rule (BJR) in the majority and dissenting opinions of Decision Number 68/Pid.Sus-TPK/2025/PN Jkt.Pst and formulates operational parameters distinguishing BJR-protected business decisions from corruption offenses under Law Number 1 of 2025. Methods: This study applies a normative juridical method that integrates statutory, case-based, and conceptual approaches to distinguish business decisions sheltered by the BJR from corruption offenses under Law Number 1 of 2025 on SOEs. Results: The majority panel held that the BJR is subject to the cumulative thresholds of Article 97(5) of the Company Law and Article 9F of the 2025 SOE Law; gross negligence (culpa lata) removes BJR protection. The dissent found no mens rea, disputed the state-loss calculation, and treated IDR 11.2 billion in due diligence as evidence of compliance. From this divergence, five cumulative parameters emerge: decision quality, degree of negligence, integrity of approval documents, character of loss, and presence of fraud or conflict of interest. Conclusion: This study offers a theoretical contribution to BJR doctrine in SOE corruption jurisprudence and provide a practical guide for Corruption Court panels in distinguishing legitimate business risk from criminal liability of SOE directors.